Background and lunar neutron populations detected by LEND and average concentration of near-surface hydrogen near the Moon's poles. (1st November 2018) - Livengood, T.A.; Mitrofanov, I.G.; Chin, G.; Boynton, W.V.; Bodnarik, J.G.; Evans, L.G.; Harshman, K.P.; Litvak, M.L.; McClanahan, T.P.; Sagdeev, R.Z.; Sanin, A.B.; Starr, R.D.; et al.
Abstract: Neutron flux measurements by the Lunar Exploration Neutron Detector (LEND) on the Lunar Reconnaissance Orbiter (LRO) enable quantifying hydrogen-bearing volatiles in the lunar surface from orbit. Accurately determining hydrogen abundance requires discriminating between the instrument background detection rate and the population of lunar-sourced neutrons that are sensitive to surficial hydrogen. We have investigated the detection rate for lunar and non-lunar (spacecraft-sourced) neutrons in LEND by modeling maps of measured count rate in three LEND detector systems using linear combinations of maps compiled from LEND detectors and from the Lunar Prospector Neutron Spectrometer. We find that 30% of the global-average 24.926 ± 0.020 neutron counts per second (cps) detected by the LEND STN3 thermal-energy neutron sensor are lunar-sourced neutrons in the thermal energy range (E < 0.4 eV), 65% are lunar-sourced neutrons in the epithermal and fast energy range (E > 0.4 eV), and 5% are from spacecraft-sourced background signal. In the SETN epithermal neutron detector, 90% of the 10.622 ± 0.002 neutron detections per second are consistent with a lunar source of epithermal and fast neutrons combined (E > 0.4 eV), with 3% due to lunar-sourced thermal neutron leakage into the detector (E < 0.4 eV), and background signal accounting for 7% of total detections. Background signal due to spacecraft-derived neutrons is substantial in the CSETN collimated detector system, accounting for 57% of the global average detection rate of 5.082 ± 0.001 cps, greater than the 48% estimated from cruise-phase data. Lunar-sourced epithermal and fast neutrons account for 43% of detected neutrons, including neutrons in collimation as well as neutrons that penetrate the collimator wall to reach the detector. We estimate a lower limit of 17% of lunar-sourced neutrons detected by CSETN are epithermal neutrons in collimation (0.37 cps), with an upper limit estimate of 54 ± 11% of lunar-sourced neutrons received in collimation, or 1.2 ± 0.2 cps global average. The pole-to-equator contrast ratio in epithermal and high-energy epithermal neutron flux indicates that the average concentration of hydrogen in the polar regolith above 80° north or south latitude is ∼105 ppmw (parts per million by weight), or 0.095 ± 0.01 wt% water-equivalent hydrogen. Above 88° north or south, the concentration increases to ∼140 ppmw, or 0.13 ± 0.02 wt% water-equivalent hydrogen. The similar pattern of neutron flux suppression at both poles suggests that hydrogen concentration generally increases nearer the pole and is not closely associated with a specific feature such as Shackleton Crater at the lunar south pole that has no northern counterpart. Epithermal neutron flux decreases with increasing latitude outside the polar regions, consistent with surface hydration that increases with latitude if that hydration extends to ∼13–40 cm into the surface. Highlights: Populations of neutrons detected by LEND on LRO constrain upper and lower limits on collimated detector capabilities. Calibration to deduce hydrogen concentration in regolith. Neutron suppression is consistent with increasing presence of H-bearing volatiles with increasing latitude. Average concentration of hydrogen within 10° of both poles is ∼105 ppmw (0.095 ± 0.01 wt% water-equivalent). Average concentration of hydrogen within 2° of both poles is ∼140 ppmw (0.13 ± 0.02 wt% water-equivalent).